Studi Kasus Asuhan Keperawatan Keluarga Pada Keluarga Tn. T Dengan Risiko Komplikasi Diabetes Mellitus Di Desa Mertan Kecamatan Mojolaban - Arifin, Fajar; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
Indonesia included in the top 10 countries with the number of people with diabetes in the world. Indonesia ranks seventh, with the number of people with diabetes as much as 4.5 million. In 2025 Indonesia in the prediction will be ranked up two places to fifth, with the predicted number of people with as many as 12.4 million people. Number of patient Diabetes in Sukoharjo Diabetes Mellitus with Insulin 605 and non-Insulin Diabetes Mellitus 6.646 people.Insulin Diabetes Mellitus Patients with highs in RSIS Yarsis with 264 people, whereas patients with non-insulin Diabetes Mellitus highest in Sukoharjo health center which amounted to 1,073 people. For in Mojolaban own people with Diabetes Mellitus with Insulin as many as 20 people and non-Insulin many as 405 people. Knowing the number of patients Diaetes Mellitus and also the relationship between knowledge and attitudes about Diabetes Mellitus in the village of the District MertanMojolaban. And to carry out measures of health education to families based on family nursing process. This research uses descriptive method. Using the nursing process a comprehensive approach that includes assessment of data, data classification, data analysis, formulation of nursing diagnosis, planning, implementation and evaluation of nursing actions. Family Tn. T say no understanding of the disease and complications from Diabetes Mellitus of Diabetes Mellitus. Ny. K also asked about swelling in the legs, sometimes feels sick and pain. Ny. K also said her vision was also rather vague ,especially when hit by sunlight. Family Tn. T say do not know exactly about what foods to avoid in order to disease Ny. K is not getting worse. For diagnosis, the risk of complications can be controlled with the objective dataNy. K understands and can explain the risk of complications of Diabetes Mellitus and Ny. K has been able to do gymnastics leg diabetes mellitus to increase blood flow in the legs often feel jimpe and pain. As for the diagnosis of the ineffectiveness of family maintenance resolved by objective dataNy. K already able to reduce the food which can raise blood sugar. After the implementasi of nursing found the advances experienced by clients. This means that action is given a positive effect on the patient in accordance with the expected goals